THE ROLE OF PROFESSIONAL COMMITMENT AND SUSPENSION OF JUDGMENT IN DECREASING AUDITORS’ PREMATURE SIGN-OFF - Andi Ina Yustina; Irina Kristela Sutarsa (Jurnal Akuntansi, 2020)
Premature sign-off is the action that can affect to reduced audit quality. The objectives of this research are to examine the effect of professional commitment and suspension of judgment towards premature sign-off. The researcher used the survey method on auditor working in a big ten public accounting firm in Jakarta. There is a total of 126 respondents who contributed to this research. The data was analyzed using Structural Equation Model-Partial Least Squares (SEM- PLS) analysis. From the data quality test results of reliability and validity test shows that all variables can be said to be valid and reliable. The result of this research shows that professional commitment affects premature sign-off and fully mediated by the suspension of the judgment of the auditors.